The Importance of Wooden Biomass in the Transition to a Bioeconomy in Latvia - Vineta Tetere; Jack Peerlings; Liesbeth Dries (Bio-based and Applied Economics, 2025)
The EU Green Deal advocates decarbonizing the EU’s energy sector, largely by transitioning to renewable sources. Latvia aims to increase renewable energy production by 10% by 2030, prioritizing biomass from forests and wood for bioenergy. This paper evaluates implementing a tax on non-biobased energy alongside a subsidy for biobased energy, particularly wood biomass, to promote its substitution as a step towards climate neutrality and energy self-sufficiency. Additionally, it examines technological advancements in the bioenergy sector. Using an applied general equilibrium model and 2015 supply and use data, the study assumes a nested production structure, enabling explicit substitution between domestic and imported inputs. Given Latvia’s heavy reliance on imported fossil fuels, these measures could lead to an 18% increase in bioenergy production, reducing CO2 emissions by 0.5 - 3.2%, and reducing fossil fuel imports by 1.04 – 3.9%.